2011
DOI: 10.2147/agg.s18695
|View full text |Cite
|
Sign up to set email alerts
|

The genomics and genetics of ankylosing spondylitis

Abstract: Abstract:The spondyloarthropathies are a group of arthritides which specifically target the spine and pelvis with ankylosing spondylitis (AS) being the most prevalent and debilitating of these conditions. Unique to AS is the progression to excessive uncontrolled bone formation following an initial inflammatory phase that can result in joint fusion and significant disability. Spondyloarthritis is estimated to affect 1%-2% of the population, twice as many as rheumatoid arthritis and thus constitutes a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 215 publications
(274 reference statements)
1
16
0
Order By: Relevance
“…This is supported by increased osteoclast numbers per trabecular bone surface in ank long bones (32). In patients affected by ankylosing spondylitis and corresponding animal models, osteopenia as a consequence of joint destruction has been well established (1,34). Normal trabecular bone values in ank vertebrae at 6 wk of age suggest that osteopenia in long bones is secondary to joint stiffness and that the joint pathology does not induce systemic bone loss at this stage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is supported by increased osteoclast numbers per trabecular bone surface in ank long bones (32). In patients affected by ankylosing spondylitis and corresponding animal models, osteopenia as a consequence of joint destruction has been well established (1,34). Normal trabecular bone values in ank vertebrae at 6 wk of age suggest that osteopenia in long bones is secondary to joint stiffness and that the joint pathology does not induce systemic bone loss at this stage.…”
Section: Discussionmentioning
confidence: 98%
“…D egenerative joint disorders like ankylosing spondylitis frequently lead to the formation of osteophytes, which finally can result in osseous ankylosis, the bridging of joints by mineralized tissue (1). This process can lead to conductive hearing loss if it affects the articulations of the hearing ossicles (2).…”
mentioning
confidence: 99%
“…AS-associated uveitis is typically anterior, meaning it most consistently affects the iris, and typically manifests as unilateral disease with recurrent episodes (3). HLA-B27 is a documented genetic susceptibility factor for AS (4), and ϳ95% of patients with AS in whom uveitis develops are HLA-B27 positive (5); however, the presence of HLA-B27 accounts for only ϳ20-40% of the genetic risk for AS. Genetics studies and clinical observations strongly suggest that uveitis is affected by additional genetic or environmental factors that distinguish it from either the axial or peripheral joint disease that is characteristic of AS (4,6).…”
mentioning
confidence: 99%
“…By effect size, we refer to the strength of the signal associated with a given genetic factor. For example, HLA (human leukocyte antigen) B27 is strongly associated with ankylosing spondylitis, particularly in patients of European descent, and accounts for a major portion of the genetic risk for this condition 24 . In contrast, a recent GWAS of human height found that height is highly polygenic, with many genes contributing small effect sizes 25 .…”
Section: Sample Selection and Statistical Powermentioning
confidence: 99%